Improving IEEE 802.11 to Support Quality of Service in Wireless Networks - Md Khambari, M. N.; Sahib, S.; Othman, M. F. I. (2007)
This paper investigates and describes the Quality of Services (QoS) provisioning techniques for IEEE 802.11 based networks, focusing on the Distributed Coordination Function (DCF). This paper propose better techniques to provide QoS by assigning new parameters to the DCF access method, involving the DCF Interframe Space (DIFS), backoff time and the maximum data packet size to high priority nodes, which will distinguish the high priority traffic from the low priority traffic to support QoS. A simulation is done using Network Simulator 2 (NS-2) and the expected output is then presented.